In vitro cytotoxic, genotoxic, and antityrosinase activities of Clitoria macrophylla root - Yamon Pitakpawasutthi; Maneewan Suwatronnakorn; Somchai Issaravanich; Chanida Palanuvej; Nijsiri Ruangrungsi (Journal of Advanced Pharmaceutical Technology & Research, 2021)
Clitoria macrophylla Wall. (Leguminosae), locally known as Non-tai-yak or An-chan-pa, commonly distributed in tropical nations and Southeast Asia. Regarding traditional Thai medical system, C. macrophylla roots carry out a potential in dermatology. Its roots are also used as insecticide in agriculture and animal farming. Moreover, clitoriacetal is the major component that can be detected in C. macrophylla root. This research aimed to assess the efficacy of C. macrophylla root extract and clitoriacetal for its anticancer and antityrosinase activities as well as to assess in vitro safety potential for its cytotoxic and genotoxic effects. C. macrophylla root and clitoriacetal were tested by brine shrimp lethality, 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay, comet assay, and antityrosinase activity. C. macrophylla root, clitoriacetal, and rotenone demonstrated the toxicity against brine shrimp nauplii with LC50 of 332.15, 136.54, and 0.15 μg/mL, respectively. C. macrophylla root and clitoriacetal showed cytotoxic potential against breast ductal carcinoma (BT-474), liver hepatoblastoma (Hep-G2), and colon adenocarcinoma (SW-620). At 100 μg/mL, the percent DNA damage of C. macrophylla root and clitoriacetal was 37.84% and 36.01%, respectively. C. macrophylla root and clitoriacetal were able to inhibit the tyrosinase enzyme with IC50 of 12.27 and 7.30 mg/mL, respectively, which less effective than glutathione (positive control). The present study revealed the in vitro biological activities of C. macrophylla root and its clitoriacetal constituent which proposed the scientific evidences in efficacy and safety evaluation including in vitro cytotoxicity, DNA damage as well as antityrosinase activities.